1989
DOI: 10.1148/172.3.953
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stenting of Completely Occluded Iliac Arteries

Abstract: Percutaneous angioplasty and placement of balloon-expandable intraluminal stents were performed in 12 iliac occlusions in 12 patients. Indications were limb salvage in seven and claudication in five. After successful stenting, ankle-brachial indexes improved by 0.15 or more in 11 of 12 patients (mean increase, 0.40), transstenotic pressure gradients decreased to less than 5 mm Hg (mean, 0.58 mm Hg) in all patients, and improvement in clinical grade was seen in all patients. At follow-up at 1-14 months (median,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(28 citation statements)
references
References 0 publications
2
24
0
2
Order By: Relevance
“…4 Similar results were reported by Gunther at al 5,6 and Murphy at al 7 Palmaz at al reported that the patency rate for the Palmaz stent at 8.7 months was 92%, and others have made a similar observation. [8][9][10][11][12] In the present study, the initial procedural success and patency rates (95% and 97%, respectively) are comparable with previous reports [4][5][6][7][8][9][10][11][12] and are considered equal to, or even superior to, the results obtained with the Wallstent or Palmaz stents.…”
Section: Discussionsupporting
confidence: 91%
“…4 Similar results were reported by Gunther at al 5,6 and Murphy at al 7 Palmaz at al reported that the patency rate for the Palmaz stent at 8.7 months was 92%, and others have made a similar observation. [8][9][10][11][12] In the present study, the initial procedural success and patency rates (95% and 97%, respectively) are comparable with previous reports [4][5][6][7][8][9][10][11][12] and are considered equal to, or even superior to, the results obtained with the Wallstent or Palmaz stents.…”
Section: Discussionsupporting
confidence: 91%
“…Recent series of primary stent placement for CTOs reported the 2-year primary and secondary or assisted primary patency rates of 69%-93% and 85%-95%, respectively. [3][4][5][6][7][8][9][10][11][12] Our series demonstrated 2-year primary and assisted primary patency rates of 91% and 96%, at the high end of the range of recent reports. However, although our patency rates for primary stents placed for iliac CTOs were better than those reported for extra-anatomic bypasses, such as axillofemoral and femorofemoral bypasses, these patency rates were not better than the patency conventionally reported for aortobifemoral bypass.…”
Section: Discussionsupporting
confidence: 47%
“…Rees et al (14) realizaram angioplastia e implante de endoprótese em artérias ilíacas ocluídas de 12 pacientes, sendo as indicações salvamento de membro em sete deles e claudicação em cinco. Tiveram taxa de falência técnica de 20%.…”
Section: Discussionunclassified